AN UPDATE CHECKLIST OF VULNERABLE FRESHWATER FISH RASBORA BALIENSIS (HUBBS & BRITTAN 1954) (CYPRINIFORMES: CYPRINIDAE) IN INDONESIA - Hasan, Veryl; Samitra, Dian (Malaysian Journal of Science, 2021)
Rasbora baliensis (Hubbs & Brattan, 1954) is a vulnerable freshwater fish from Indonesia which was described in East Java, Bali Island, and West Lesser Sunda Islands. Specimens of R. baliensis were collected from several new Rivers in Java and East Lesser Sunda Islands and shows the current distribution range of this species.